Manual de judicialização do direito ao trabalho do reeducando: proposta de criação de indústria prisional autossustentável em municípios com mais de 250 mil habitantes - Gonçalves, Ricardo Gomes Quintana (Universidade Federal do Tocantins, 2021)
This technical report aims to register the activities developed during the Post Graduation Program in Jurisdictional Provision and Human Rights (PPGPJDH) of the Federal University of Tocantins (UFT) in partnership with the Superior School of Judges of Tocantins (ESMAT), for the preparation of the Manual of Judicialization of the Right to Work of the Inmate in Self-Sustainable Prison Industry in Municipalities with More than 250 Thousand Inhabitants, so that state and municipal organs such as Public Prosecutor's Office, Public Defender's Office, Executive Power, Judiciary Power and other social actors of the community, in a multipolar process involving the violation of the fundamental right of the prisoner under State custody, may guarantee him decent work, in order to remit and enjoy the educational and productive purpose of the penalty, and, consequently, collaborate with the reduction of the criminal recidivism rate.